The theory of abrogation : a critical evaluation - Khan, Israr Ahmad (Research Centre, International Islamic University Malaysia, 2006)
Abrogation (naskh) in the Qur'an constitutes one of the most controversial issues in the Islamic legacy. There are two groups of scholars, one supporting it and the other denying its existence in the Qur'an. A number of works representing both the views are available. This work attempts to critically analyze the arguments and the views of the supporters of the theory of nasakh, advancing a crystal clear picture that the concept of naskh in the sense of permanent abrogation hence practical invalidity of certain ayat in the Qur'an, either five (5) or five hundred (500), is untenable. All the reports concerning the views of sahabah and tabi'un scholors have been scrutinized in two chapters of this book. Most of these reports are unreliable from both the sanad (chain) and the matan (text) angles. Certain traditions reporting the matter concerning naskh appear to be authentic from sanad point of view but from the dimension of the matn they may not be acceptable. This work represents a humble endeavor of the author to prove the everlasting practical validity of each and every single statement of the Qur'an. The notion of naskh in the Qur'an starkly contrasts with the fact that the Qur'an is al-haqq (the truth) from the Lord of the universe. The author has made a modest effort to highlight and reassert the same undeniablity valid reality that the Last Revelation of Allah is the truth, hence the claim of availability of abrogated rulings in the Qur'an may be considered valid.